E-Government And Trust In Public Administration From The Perspective Of E-Notifikasi Users - Zulkifli, Zarina (2021)
Trust in public administration has been declining over the years. Inefficiency and poor service delivery were identified among the factors that contributed to this problem. In this case, e-government related activities were proposed to rebuild citizens’ trust levels in public administration. This research was carried out to examine the relationship between e-government related activities and trust in public administration by targeting the users of the e-notifikasi system Ministry of Health, Malaysia. A conceptual framework was developed and validated through 382 screened sets of self-administered questionnaire. Data analysis using SmartPLS software revealed that trust in public administration was influenced by e-service quality and public administration communication. The attitude towards e-government mediated the relationship between independent variables and trust in public administration. Gender only moderated the relationship between e-service quality and trust in public administration. The results contributed to a new body of knowledge in examining the relationship between e-government activities and trust in public administration. The study demonstrated gender imbalance between male and female respondents for the moderator analysis. The study results suggested that more studies need to be conducted to discover the associations between all the variables, particularly in the Malaysian context.